Globalization and Cooperation: The New Global Infrastructure Formation - Elena Vyacheslavovna ZENKINA; Valery Maksimovich TUMIN; Natalya Vladimirovna IVINA; Petr Aleksandrovich KOSTROMIN1 (Communications of International Proceedings, 2021)
At present, the globalization processes have led to a new global infrastructure’s creation based on the cooperation’s mechanisms between the powers and their solidarity. This is due to the fact that the modern global economy’s development involves the competitiveness concept’s traditional interpretation transformation. Today, the countries’ and companies’ competitive positions have become the ability to cooperate, be a partner, and work together on projects. This is confirmed by the coronavirus epidemic that has engulfed the whole world, which can be defeated only through the \scientific knowledge’s exchange, cooperation and global mutual assistance. The article provides a literary review of historical views on the globalization’s concept and its place in the modern economic relations’ system. The globalization index’s dynamics, the world trade’s and GDP’s development in the conditions of COVID-19 are presented. The globalization’s pros and cons are characterized. The intellectual capital’s importance for the competitive globalized development of companies, territories and countries is noted. The article considers the globalization’s practice in the digital business’ era. Conclusions are drawn about the cooperation’s importance for increasing the international globalization market mechanisms’ stability.
Keywords: World Economy; Globalization; Economic Development Trends; International Cooperation.